THE IMPACT OF THE TRANSITION OF PROHIBITED FOREST TO PAGERWUNUNG NATURE RESERVE ON CHANGES IN URBAN LEGEND IN DARUPONO VILLAGE KALIWUNGU KENDAL IN 2004 - Risa Nur Sikhah; Ita Dwijayanti (Vol. 2 No. 1 (2024): Proceeding of International Conference on Cultures & Language 2024, 2024)
Known as the forbidden forest, in 1965 it was used as a massacre place for people accused by the Indonesian Communist Party (PKI). This gives the impression of being haunted and gives birth to myths that develop in society. In 2004, the Kendal Regency government and Perhutani collaborated in the process of changing the name of the prohibited forest to a nature reserve. This research aims to find out the history and process of transitioning prohibited forests into nature reserve areas, in order to obtain several factors that influence the transition, as well as the impact felt by the surrounding community regarding urban legends related to Kendal Regency. The method used in this research is a historical-qualitative method, which consists of heuristics (data collection by interviewing related parties and also collecting sources of oral history of the Kendal community, namely urban legends), verification (critique of sources, this is done by limiting observations research so that the focus is on the three objectives of this research carried out), interpretation (analysis carried out by creating a structured narrative whose truth and novelty can be accounted for), and historiography (carried out to convey the results of observations in three chapter discussions which will be completed in approximately 2-6 months) . The results of the research show that before and after being converted into a nature reserve area, this place had the impact and beliefs of urban legends that were formed by the surrounding community based on certain age groups. The process of transitioning prohibited forests into nature reserve areas is in accordance withMinister of Forestry Decree Number: SK. 115/Menhut-II/2004 as a nature reserve area. Until 2024, the percentage of visitors in the nature reserve area will increase to 45% with many sellers around the nature reserve. This shows that promoting historical tourism with positive urban legends can attract visitors and increase regional income and the income of the surrounding community.